Dietary Pleurotus citrinopileatus Polysaccharide Improves Growth Performance and Meat Quality Associated with Alterations of Gut Microbiota in Arbor Acre Broilers - Nannan Zhou; Xiaoxiao Song; Changxi Wu; Shuangmin Liang; Liangyu Yang; Changrong Ge; Zhichao Xiao (Foods)
Adding edible fungal polysaccharides to animal diets improves growth performance, meat quality, intestinal health, and immunity without adverse effects. This study aimed to evaluate the impact of Pleurotus citrinopileatus polysaccharide (PCP, including PCP250, PCP500, PCP750, and PCP1000 mg/kg) on the growth performance, meat quality, and microbial composition of Arbor Acre (AA) broilers (total 180) by metabolomics and high-throughput sequencing. The results showed that adding PCP enhanced chicken meat tenderness, redness (a*), and water retention and raised essential amino acids and flavor amino acids (such as umami and sweet amino acids) content. The metabolomics revealed that IMP, creatine, betaine, sarcosine, and taurine were related to improving meat quality in broilers by PCP addition. In addition, amino acid, purine, and lipid metabolism were the main metabolic pathways. Moreover, PCP could regulate muscle metabolism by increasing the relative abundance of Lachnospiraceae and Lactobacillus and the content of short-chain fatty acids (SCFAs). Therefore, PCP may become a promising new dietary supplement in the future, which may improve the yield and quality of broiler chickens.